Pengaruh Mental Accounting Pada Generasi Z Terhadap Financial Behaviour Pada Masa Pandemi Covid 19 dengan dimediasi Gaya Hidup - Deasy Lestary Kusnandar; Dian Kurniawan; Nana Sahroni (Valid: Jurnal Ilmiah, 2022)
Along with the lifestyle changes experienced by the community, it has an influence on people's behavior, especially behavior in managing finances. With the increase in one's lifestyle, it will cause problems in financial management. Ideally, mental accounting and lifestyle factors can influence a person's behavior in managing finances. Mental accounting will shape one's financial behavior well. This study aims to determine the effect of mental accounting on financial behavior with lifestyle as a mediating variable. This research is a type of quantitative research using a survey method given to Generation Z who have used e-wallet or e-money. Determination of the number of samples in this study were as many as 300 respondents with the sampling method used was using judgment sampling. The analysis used is Structural Equation Modeling (SEM) analysis. The results show that financial literacy affects lifestyle, mental accounting affects lifestyle, and lifestyle mediates financial literacy and mental accounting on financial behavior.